Search Engine Optimization - Veglis, Andreas; Giomelakis, Dimitrios (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue book focuses on the theory and practice of search engine optimization (SEO). It is intended for anyone who publishes content online and it includes five peer-reviewed papers from various researchers. More specifically, the book includes theoretical and case study contributions which review and synthesize important aspects, including, but not limited to, the following themes: theory of SEO, different types of SEO, SEO criteria evaluation, search engine algorithms, social media and SEO, and SEO applications in various industries, as well as SEO on media websites. The book aims to give a better understanding of the importance of SEO in the current state of the Internet and online information search. Even though SEO is widely used by marketing practitioners, there is a relatively small amount of academic research that systematically attempts to capture this phenomenon and its impact across different industries. Thus, this collection of studies offers useful insights, as well as a valuable resource that intends to open the door for future SEO-related research.